2004
DOI: 10.1128/mcb.24.8.3089-3099.2004
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Function of the Amino-Terminal Inhibitory Domain of TAF1 in Transcriptional Regulation

Abstract: The general transcription factor TFIID is composed of TATA-binding protein (TBP) and 14 TBP-associated factors (TAFs). TFIID mediates the transcriptional activation of a subset of eukaryotic promoters. The N-terminal domain (TAND) of TAF1 protein (Taf1p) inhibits TBP by binding to its concave and convex surfaces. This study examines the role of the TAND in transcriptional regulation and tests whether the TAND is an autonomous regulator of TBP. The TAND binds to and regulates TBP function when it is fused to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…All strains used in S1 Fig were derived from Y22.1, which carries a deletion of the chromosomal TAF1 coding region and the wild-type TAF1 gene in a URA3 -based low-copy-number vector (pYN1) [ 39 ]. YTK2741 [ 40 ] and YTK3778 were generated from Y22.1 by replacing pYN1 with pM1169 (HA-tagged wild-type TAF1 /pRS314) [ 41 ] and pM1746 (HA-tagged taf1-N568Δ /pRS314), respectively. The latter plasmid was constructed by site-directed mutagenesis of pM1169 using the primer TK176 [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…All strains used in S1 Fig were derived from Y22.1, which carries a deletion of the chromosomal TAF1 coding region and the wild-type TAF1 gene in a URA3 -based low-copy-number vector (pYN1) [ 39 ]. YTK2741 [ 40 ] and YTK3778 were generated from Y22.1 by replacing pYN1 with pM1169 (HA-tagged wild-type TAF1 /pRS314) [ 41 ] and pM1746 (HA-tagged taf1-N568Δ /pRS314), respectively. The latter plasmid was constructed by site-directed mutagenesis of pM1169 using the primer TK176 [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that TAND of TAF1 could act independently from the rest of the molecule (46). The functional autonomy of TAND was tested by fusing it to the N or C termini of several other components of TFIID and it was found to have similar function as at the N terminus of TAF1.…”
Section: Discussionmentioning
confidence: 99%
“…1). Our recent studies suggest that TAND of TAF1 is an autonomous regulator of TBP function (46). TAND can interact with and regulate TBP function when it is fused to either termini of any TFIID subunit.…”
mentioning
confidence: 99%
“…Immunoblotting and preparation of the polyclonal antibodies directed against Spt3, Taf11, and TBP were described previously (Tsukihashi et al. 2000; Takahata et al. 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Two dimensional blue-native PAGE (BN-PAGE) (Wittig et al 2006) was conducted with precast Native PAGE 3%-12% gel in the first dimension and precast NuPAGE 4%-12% Bis-Tris Zoom gel in the second dimension, according to manufacturer's instructions (Invitrogen). Immunoblotting and preparation of the polyclonal antibodies directed against Spt3, Taf11, and TBP were described previously (Tsukihashi et al 2000;Takahata et al 2004). Polyclonal antibodies directed against Toa1 (aa 1 to 286), Sua7 (aa 1 to 345), Med4 (aa 1 to 284), Med6 (aa 1 to 295), Med7 (aa 1 to 222), Med9 (aa 1 to 149), Med11 (aa 1 to 132), Med15 (aa 1 to 300), Med17 (aa 1 to 300), Med19 (aa 1 to 220), Med20 (aa 1 to 210), Med22 (aa 1 to 121), Cdk8 (aa 1 to 555), Rpb3 (aa 1 to 318), Tfa1 (aa 1 to 482), and Tfg2 (aa 1 to 400) were raised in rabbits using recombinant, gel-purified His-tagged polypeptides expressed in E. coli as antigens.…”
Section: Immunoblot Analyses and Antibodiesmentioning
confidence: 99%